2019
DOI: 10.5812/jkums.92027
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Vein Cutdown in Infants with no Other Vascular Access Admitted to Mohammad Kermanshahi Hospital

Abstract: Background: Umbilical vein cutdown in neonates as an important method of accessing vascular is very important in cases in which peripheral vein is not available and it is not possible to cut down another vein. The umbilical vein is believed to become thrombotic and lumen is closed and unusable one week postpartum. Methods: In this cross-sectional study, all neonates who were admitted to the surgical ward of Mohammad Kermanshahi Hospital in Kermanshah, who needed emergency vein access and who were unable to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…27 , 28 , 43 Nevertheless, the final diagnosis is more accurate with a combination of the patient’s clinical condition and various laboratory parameters. Regarding sonography, the research conducted by Amanollahi et al found that the sensitivity and specificity were 98% and 76%, which is similar to our study, 26 while some other studies have reported sensitivity and specificity of less than 60% for sonography. 27 , 36 The differences in the diagnostic accuracy of sonography can be explained in terms of the differences in the operator’s skill and the level of cooperation of the patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27 , 28 , 43 Nevertheless, the final diagnosis is more accurate with a combination of the patient’s clinical condition and various laboratory parameters. Regarding sonography, the research conducted by Amanollahi et al found that the sensitivity and specificity were 98% and 76%, which is similar to our study, 26 while some other studies have reported sensitivity and specificity of less than 60% for sonography. 27 , 36 The differences in the diagnostic accuracy of sonography can be explained in terms of the differences in the operator’s skill and the level of cooperation of the patients.…”
Section: Discussionsupporting
confidence: 91%
“…25 The findings of the studies conducted in populations consisting of children and adults, such as the study by Amanollahi et al and Erfani Fam et al, also indicated a frequency of 10 to 15% for negative appendectomies. 26 , 27 In the study by Yazar et al, the prevalence of negative appendectomies in the adult population was reported to be 11%. 28 Another study conducted in 2016 in China stated that the rate of negative appendectomies in the adult population was 25%, 29 while Khorshidi et al in Hamedan reported that the rate of negative appendectomies in adult patients was about 70%.…”
Section: Discussionmentioning
confidence: 99%